Facile synthesis of annulated benzothiadiazole derivatives and their application as medium band gap acceptors in organic photovoltaic devices. Issue 24 (8th June 2022) - Hu, Xiantao; Datt, Ram; He, Qiao; Kafourou, Panagiota; Ka Hin Lee, Harrison; White, Andrew J. P.; Tsoi, Wing Chung; Heeney, Martin
Abstract : Two benzothiadiazole derivatives annulated with 2-(1, 3-dithiol-2-ylidene)malonitrile in the 4, 5-position were prepared by a one-step procedure, and investigated as end-groups in non-fullerene acceptors for indoor photovoltaic applications. Abstract : Two 2, 1, 3-benzothiadiazole derivatives annulated with 2-(1, 3-dithiol-2-ylidene)malonitrile in the 4, 5-positions were prepared by nucleophilic substitution reactions of a fluorinated precursor. The resulting derivatives were coupled to an electron rich indacenodithiophene core to afford two new non-fullerene acceptors (NFAs). Both NFAs exhibited identical absorption spectra in solution, but significant differences in the solid state as a result of the end group fluorination. Both materials performed as electron acceptors in solar cell blends with donor polymers. The resulting devices exhibited high open circuit voltages over 1 V under 1 sun illumination, as a result of their high lying LUMO levels. Devices based on the fluorinated acceptor demonstrated reasonable performance under low light conditions, with power conversion efficiencies up to 13.7%.